2012
DOI: 10.1021/jp301140u
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-Grained Modeling of the Self-Association of Therapeutic Monoclonal Antibodies

Abstract: Coarse-grained computational models of two therapeutic monoclonal antibodies are constructed to understand the effect of domain-level charge-charge electrostatics on the self-association phenomena at high protein concentrations. The coarse-grained representations of the individual antibodies are constructed using an elastic network normal-mode analysis. Two different models are constructed for each antibody for a compact Y-shaped and an extended Y-shaped configuration. The resulting simulations of these coarse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
200
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(207 citation statements)
references
References 41 publications
7
200
0
Order By: Relevance
“…21,22,24,25,39 Few reports, however, have implicated the Fc region in mediating mAb RSA. 23,26 Nishi et al used low resolution biophysical tools to show the involvement of the Fc region in mediating reversible Fc-Fc interactions between mAb monomers. Chaudhri et al used coarse-grained molecular dynamic simulations to probe the nature of site-site interactions between mAb monomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22,24,25,39 Few reports, however, have implicated the Fc region in mediating mAb RSA. 23,26 Nishi et al used low resolution biophysical tools to show the involvement of the Fc region in mediating reversible Fc-Fc interactions between mAb monomers. Chaudhri et al used coarse-grained molecular dynamic simulations to probe the nature of site-site interactions between mAb monomers.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous work has shown that reversible self-association (RSA) between different IgG1 mAbs can result from different binding interfaces, despite high sequence similarity between the mAbs. [20][21][22] Studies of enzymatic fragmentation of IgG1 monomers into Fab and Fc domains, 21,23,24 site-specific mutations in complementaritydetermining region (CDR), 25 and coarse-grained simulations of such protein interactions 26,27 suggest that intermolecular reversible interactions between mAb molecules can be initiated by either Fab-Fab or Fab-Fc associations and to a lesser extent through FcFc interactions. Despite providing experimental insights into how solution conditions modulate the rate and extent of reversible protein-protein interactions, and which major regions of the mAb might be involved in such phenomena, these studies offer an incomplete and low-resolution picture of mAb reversible self-association.…”
Section: Introductionmentioning
confidence: 99%
“…57 In general, coarsegraining of a biological macromolecule should be performed in a manner that retains reasonably accurate descriptions of the properties of interest while ignoring the others. [57][58][59] Chaudhari et al 60,61 studied concentration-dependent solution behavior of two antibodies with different levels of coarsegraining and Buck et al 42 extended Chaudhari's approach to four different mAbs. Because of the small number of beads per antibody molecule and absence of explicit solvent molecules, these authors were able to put several hundred antibody molecules in a simulation box and perform molecular dynamics simulations over micro-second time scales.…”
Section: Multi-scale Molecular Simulations Of Antibody Solutions To Umentioning
confidence: 99%
“…Such simulations may be useful in designing MAbs with improved solution behavior at high concentrations since specific regions of interactions can be identified (see figs. 7 and 8 in Chaudhri et al 2012) …”
Section: Dilute Solution Static and Dynamic Light Scattering Measuremmentioning
confidence: 99%
“…Reproduced from Yadav et al (2011c) self-association at high concentration, coarse-grained computational models of MAb 1 and MAb 2 were constructed. Two reduced coarse-grained (12-and 26-site) models were constructed for each antibody using either a compact Yshaped or an extended Y-shaped configuration, and coarsegrained molecular dynamics simulations as described by Chaudhri et al (2012) were carried out. Overall, the 12-and 26-site models compared very well with each other, and the choice of a compact versus extended structure did not alter the results or conclusions.…”
Section: Dilute Solution Static and Dynamic Light Scattering Measuremmentioning
confidence: 99%